The Italian's final redemption - Ashenden, Jackie (Harlequin presents, 2020)
"Vincenzo de Santi has dedicated his whole life to redeeming his family's crimes. So when Lucy Armstrong offers evidence about her nefarious father in exchange for her freedom, he will show no mercy. No matter how innocent she seems... Lucy must escape her father's prison, even if that means bargaining with another powerful man. Yet for all Vincenzo proclaims to be coldhearted, his touch is red-hot. For once, Lucy isn't afraid. However, before Vincenzo can set her free, first she must free him..."--Provided by publisher.